Infrared Thermography Reveals Sex-Specific Responses to Stress in Mice - Faraji, Jamshid; Metz, Gerlinde A. S. (Frontiers in Behavioral Neuroscience, 2020)
Psychogenic hyperthermia is a stress-related condition reported mostly in women. Neuroendocrine responses to stress in females differ from those in males, and these differences cannot be explained solely based on hypothalamic-pituitary-adrenal (HPA) axis activity. Here, we used infrared (IR) thermographic imaging to record changes in cutaneous temperature following two types of stressful experiences in female and male mice. Mice were exposed to either single-session restraint stress or vertical exploration (rearing) deprivation and were monitored for exploratory activity and IR surface thermal changes. Females displayed higher rearing activity than males during the dark phase of the light cycle. Both sexes showed similar plasma corticosterone (CORT) responses after a challenge with restraint and rearing deprivation. However, only females responded to rearing deprivation with increased cutaneous temperature in the head and back, and a reduced thermal response in the tail. Circulating CORT levels were not correlated with the thermal variations. These findings, for the first time, provide evidence for sex-specific cutaneous thermal responses to short-term stress in mice following transient vertical-activity deprivation that may mimic clinical psychogenic hyperthermia.